Antibacterial Effect of Synthetic Peptide LyeTxI and LyeTxI/β‐Cyclodextrin Association Compound Against Planktonic and Multispecies Biofilms of Periodontal Pathogens. Issue 6 (1st June 2017) - Cruz Olivo, Edison Andrés; Santos, Daniel; de Lima, Maria Elena; dos Santos, Vera Lúcia; Sinisterra, Rubén Dario; Cortés, María Esperanza
Abstract : Background: Antimicrobial peptides (AMPs) have shown rapid and potent effect against planktonic bacteria. However, control of periodontopathic biofilms is a challenge even for AMPs. Thus, the present study evaluates in vitro antimicrobial activity of synthetic peptide LyeTxI and association compound LyeTxI/β‐cyclodextrin (βCD) against multispecies biofilms. Methods: Sensibility to LyeTxI and LyeTxI/βCD was determined for planktonic Gram‐negative periodontopathogens. Time‐kill kinetic assay was performed at minimum inhibitory concentrations (MICs) in all planktonic strains. Multispecies biofilms were grown on pegs using a biofilm device and studied by scanning electron microscopy at 2, 5, and 10 days. Minimal biofilm eradication concentration (MBEC) was determined for 2‐ and 4‐day multispecies biofilms. Metabolic activity of biofilms was determined by fluorometry study. Results: Biofilms showed reproducible cell density on pegs of the biofilm device. LyeTxI and LyeTxI/βCD were active against all strains tested at concentrations ≤62.5 μg/mL. Kinetic assays showed rapid bactericidal effect of LyeTxI against all periodontopathogens. MBECs of LyeTxI and LyeTxI/βCD against multispecies 2‐day biofilms were two‐fold higher than MICs of cells shed from biofilms. LyeTxI was able to reduce multispecies 2‐day metabolic activity by 90%. Multispecies 4‐day biofilms were tolerant to all agents tested. Conclusions: LyeTxI and LyeTxI/βCD are active against periodontopathic bacteria, showing rapid bactericidal effect and may be used to prevent biofilm development. In the future, AMPs could be therapeutic tools for treatment of periodontitis.